Use of Robots in Dentistry: A Fact or a Fiction - Sangram Panda (Indian Journal of Forensic Medicine & Toxicology, 2020)
Robotics is the most enthralling example of human invention which has the potential to replace the humanfactor altogether. Slowly but surely this invention is also making its way in dentistry too. The robotics coupledwith artificial intelligence is being modified and customized to be used in the Dentistry. The advantage ofrobotic technology includes precision work delivered in a fatigue-less manner. This paper revisits the presentuse of robotic technology in dentistry and its future applications.